Evolving Roles of Outstanding School Heads in Meeting the Challenges of the New Normal: A Phenomenological Study - Dr. Merly J. Sarzoso; Dr. Marcial M. Bandoy; Dr. Albert A. Yazon; Consorcia S. Tan; Dr. Lerma P. Buenvinida (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
The study mainly focused on determining the evolving roles of the outstanding school heads in meeting the challenges of the new normal. It also aimed to develop a compendium of best practices to help the school leaders in addressing the difficulties they are encountering in the new normal. This qualitative research utilized phenomenology as an approach. There are 10 outstanding school heads - participants who were chosen through purposive sampling by which the participants share common experiences. The researcher used validated semi-structured interview guide questions as the main instrument, and a one-on-one interview was conducted in order to obtain meaningful data. The data were transcribed and coded for the researcher to come up with the emerging themes. The themes that emerged from the testimonies of the participants were clustered into a superordinate theme: Plugged in surveillance, evince reciprocity, paradigmatic positive alacrity, and fondness of diversity. Moreover, a compendium of best practices was developed to provide opportunities and tools for the school leaders in addressing and meeting the challenges in the new normal in education. The results of the study can be used by the school heads in addressing the challenges that they are facing in different circumstances like this pandemic. Their roles are becoming broader and spiced up by some complications brought about by the need to be more responsive and able to maintain the quality characteristics of basic education services primarily wielded out by teachers and with the support of local stakeholders in these most trying times of pandemic. A compendium of best practices is necessary since it will serve as the guide of the school heads in providing solutions to the existing problems because of the pandemic, and at the same time, it will be their framework in replicating and adapting the best practices shared by the participants.